Entrepreneurial Opportunities and Poverty Alleviation - Alvarez, Sharon A.; Barney, Jay B. (Entrepreneurship Theory and Practice, 2014)
Entrepreneurial activity does not always lead to economic growth. While improvements have been made to human capital, property rights protection, and access to financial capital in abject poverty contexts with the assumption that they will increase entrepreneurial activity, the results have been mixed. More recently, many entrepreneurs interested in poverty alleviation are crossing borders to engage in initiatives aimed at reducing poverty internationally. These efforts have also had mixed results. This paper posits that one reason is that entrepreneurial opportunities and their wealth creation potential vary, and the impact of exploiting these opportunities on economic growth in poverty contexts can also vary. This paper identifies self–employment opportunities, often exploited in abject poverty, that do not lead to sustainable growth solutions. Alternatively, discovery and creation opportunities while difficult to exploit in poverty contexts hold the greatest potential for significant economic impact.